CLIMATE CHANGE IN CENTRAL ASIA AND ITS EFFECTS ON THE GREEN ECONOMY - Sanakulov Mukhriddin Sadriddinovich (TADQIQOTLAR.UZ, 2024)
Annotation The  article  highlights  the  impact  of  climate  change  on  Central  Asia  and  its implications  for  the  region's  transition  to  a  green  economy.  It  explains  how  rising temperatures, glacial melting, water scarcity, and extreme weather events threaten the environment  and  socio-economic  stability.  The  green  economy  is  presented  as  a solution, focusing on renewable energy, sustainable agriculture, green infrastructure, and  regional  cooperation.  The  article  also  addresses  the  challenges  of  funding, dependence  on  fossil  fuels,  and  political  instability,  offering  insights  into  policy innovation and international collaboration. Central Asia is experiencing significant climate change impacts, including rising temperatures, water scarcity, and land degradation, which threaten its environment and economy. This article explores how these challenges influence the region's shift toward a  green  economy.  It  identifies  opportunities  in  renewable  energy,  sustainable agriculture,  and  green  infrastructure  while  emphasizing  the  need  for  regional cooperation. Despite progress, barriers such as limited funding and fossil fuel reliance persist. By adopting effective policies and leveraging international support, Central Asia can achieve sustainable growth and resilience against climate challenges.